Independent resolving sets in graphs. Issue 2 (4th May 2021) - Suganya, B.; Arumugam, S.
Abstract: Let G = ( V, E ) be a connected graph. Let W = { w 1, w 2, …, w k } be a subset of V with an order imposed on W . The k -vector r ( v | W ) = ( d ( v, w 1 ), d ( v, w 2 ), …, d ( v, w k ) ) is called the resolving vector of v with respect to W . The set W is called a resolving set if r ( v | W ) ≠ r ( u | W ) for any two distinct vertices u, v ∈ V . In this paper we investigate the existence of independent resolving sets in Cartesian product and corona of graphs.